Estresse eletromecânico em transformadores sob o enfoque de curtos-circuitos assimétricos : uma abordagem analítica e computacional - Barra, Pedro Henrique Aquino (2017)
The transmission and the distribution of electric energy require power transformers, which are considered essential units in electrical power systems. Through a process known electromagnetic conversion, the transformers adjust the voltage and current levels according to each identified need. For this reasons, a transformer is one of the most expensive elements in an electric power system. Failures in these devices can cause onerous financial damages related to replacement of them, problems with the power supply, production downtime and decline in the quality indicators as well as another consequences. Failures caused by mechanical stress due to transient currents in the transformers windings are important aspects to be considered because they can reduce the transformers lifetime or even cause irreversible damages of them. Therefore, it is crucial to analyze and control the mechanical conditions of the windings, especially those which have been used for a long period of time, to avoid the number of unexpected failures. In this study, an analytical method involving some techniques, methodologies and strategies is presented to understand the electromechanical efforts in transformers and to evaluate the failures due to radial and axial forces. In this way, this work aims at investigating the electromechanical efforts from energizations, symmetrical faults and unsymmetrical faults - the last one is still unexplored in the literature. Concerning the data above referred, a transformer is modeled in Finite Element Method Magnetics (FEMM), based on the Finite Element Method (FEM). From the computational simulations, the magnetic behavior of the transformer faced these events is also investigated. Besides, the severities of the events are compared to each other through the Euclidean distance concept. Finally, it is presented a strategy for evaluating the safety margin of transformers operation from a mechanical withstand perspective, through some case studies.